2018
DOI: 10.5130/ajceb.v18i4.6362
|View full text |Cite
|
Sign up to set email alerts
|

Compliance within a Regulatory Framework in Implementing Public Road Construction Projects

Abstract: The construction industry faces a lack of compliance with policy that in Uganda public road construction projects affects the attainment of Government goals and disrupts infrastructure project delivery. For decades, public entities have been known for a lack of compliance that manifest in: poor performance, poor personnel management, poor resource utilization and unprofessionalism. In Uganda, this has resulted in several restructures aimed at improving service delivery. Despite this, compliance remains an issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 61 publications
4
18
0
2
Order By: Relevance
“…The study of Jaafar et al (2016) also found the strong influence of professionalism and compliance with public procurements in Malaysia. This is also consistent with the findings of Mrope (2017) among Tanzanian public institutions, as well as Kenya (Jones et al, 2015) and Uganda (Mwelu et al, 2018). However, an earlier study of Eyaa and Oluka (2011) reported insignificant effects of professionalism on compliance with public procurement.…”
Section: Professionalism Ethical Behavior and Compliance With Public Procurement Regulationssupporting
confidence: 88%
See 2 more Smart Citations
“…The study of Jaafar et al (2016) also found the strong influence of professionalism and compliance with public procurements in Malaysia. This is also consistent with the findings of Mrope (2017) among Tanzanian public institutions, as well as Kenya (Jones et al, 2015) and Uganda (Mwelu et al, 2018). However, an earlier study of Eyaa and Oluka (2011) reported insignificant effects of professionalism on compliance with public procurement.…”
Section: Professionalism Ethical Behavior and Compliance With Public Procurement Regulationssupporting
confidence: 88%
“…The review above revealed consistent relationship between professionalism and compliance with public procurement regulations (Gelderman et al, 2006;Jaafar et al, 2016;Jones et al, 2015;Mrope, 2017;Mwelu et al, 2018;Omagbon, 2016;Sandada and Kambarami, 2016). As such, the literature established that whena consistent relationship has been identified between variables, there is a need to understand the mechanism that underpins such a consistent relationship.…”
Section: Professionalism Ethical Behavior and Compliance With Public Procurement Regulationsmentioning
confidence: 82%
See 1 more Smart Citation
“…There are other areas of procurement that require regulatory compliance in general, but compliance of procurement laws and regulations is an area of interest. Studies centred on the compliance of procurement laws and regulations including but not limited to Eyaa and Oluka (2011), Mwelu et al (2018, 2020), Osei-Tutu et al (2011), Pastory (2019), Sarawa and Mas’ud (2020). This is because procurement regulatory compliance enhances the performance of procurement in procuring entities (Athumani and Minja, 2017).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…There have been efforts made over time by construction organizations to ensure their activities are carried out in a manner that is not harmful to the natural environment. These efforts are mostly borne out of a desire to preserve the natural environment, or in a bid to meet the minimum acceptable standards of environmental performance, as spelt out in both local and international regulations (Mwelu et al, 2018). The efforts of these construction organizations have yielded mixed results.…”
Section: Introductionmentioning
confidence: 99%